Monitoring Immune Dysfunction in Critically Ill Patients with Carbapenem-Resistant Acinetobacter baumannii Sepsis Treated with Regimens Including Cefiderocol: A Pilot Study to Identify Accessible Biomarkers to Stratify Patients’ Prognosis - Antonella Frattari; Ennio Polilli; Laura Timelli; Francesca Spagnuolo; Paolo Fazii; Giustino Parruti (Antibiotics)
Background: Multidrug-resistant Acinetobacter baumannii (CRAB) infections are a serious problem in critical care. This study aims to develop an early prognostic score for immune paralysis, using practical and cost-effective parameters, to predict ICU mortality in patients with CRAB infections being treated with Cefiderocol. Methods: We carried out an observational pilot study on consecutive patients hospitalized in the ICU with ensuing septic Acinetobacter baumannii infections treated with Cefiderocol monotherapy or Cefiderocol including combinations. We investigated the predictive power of lymphocyte counts, lymphocyte subpopulations, serum cholinesterase levels, and reactivation of herpes viruses. Results: Overall, 36 of 39 patients entered in our analysis: 20 survivors and 16 deceased. A total of 12 patients developed bacteremia, 19 patients had HAP/VAP, and 5 patients had a soft tissue infection. Univariate analyses of factors associated with unfavorable outcome revealed a significant association for age (OR: 1.5, CI: 1.11–2.02), SAPS II (OR: 1.05, CI: 1.01–1.1), SOFA score (OR: 1.37, CI: 1.06–1.76), lymphocytopenia (OR: 32.5, CI: 3.45–306.4), viral reactivation (OR: 9.75, CI: 1.72–55.4), and cholinesterase drop <1600 U/L (OR: 39.7, CI: 5.8–271.6). At variance, monotherapy or associations with Cefiderocol were not associated. In the final multivariable model, the only independent predictors of death were age (OR: 1.42, CI: 0.98–2.05), lymphocytopenia (OR: 18.2, CI: 0.87–371), and cholinesterase drop to below 1600 U/L (OR: 9.7, CI: 0.77–123.7). Conclusions: Age, lymphocytopenia, and serum cholinesterase drops, which were nearly significantly associated with an unfavorable outcome, may help pinpoint patients with acute immune paralysis during sepsis. Knowledge of such an immune state may in turn directly influence patients’ care.